The Wiley-Blackwell companion to inter-religious dialogue - Cornille, C. (Wiley-Blackwell companions to religion, 2013)
"This comprehensive volume brings together a distinguished editorial team, including some of the field's pioneers, to explore the aims, practice, and historical context of interfaith collaboration. Explores in full the background, history, objectives, and discourse between the leaders and practitioners of the world's major religions Examines relations between religions from around the world, moving well beyond the common focus on Christianity, to also cover over 12 major religions Features a wealth of case studies on contemporary interreligious dialogue Charts a long-term shift away from a competitive rivalry between belief systems, and a change in focus towards the more respectful, cooperative approach reflected in institutions such as the World Council of Churches Includes up-to-date commentary on the growing dialogue of recent years, written by some of the leading figures working in the field of interfaith discourse "--